Positive psychology and self-help popular psychology: a historical, psychological and cultural romance - Cabanas, Edgar; Huertas, Juan A. (Anales de Psicología / Annals of Psychology, 2014)
In this paper, the psychological discourse about the subject provided both by positive psychology and by self-help literature is compared. To specify the object of analysis we define a set of psychological categories and subcategories, to which we have dubbed as “positive” individualism and which cultural and historical back-ground has been analyzed in previous works. Besides these categories, we analyze other aspects such as the kind of vocabulary and the type of rhetoric deployed by both kind of literature to defend their arguments. To carry out these analyses we used a mixed methodology, combining the word-count technique, the ANOVA, the correspondences analysis, and key-words in context. We added a critic discussion of the texts to the data obtained. The hypothesis set out here postulate that both positive psychology and self-help literature share common psychological roots: they defend the same idea of happiness in a similar way psychological concepts in order to describe and explain the individual, and develop analogous psychological practices and techniques aiming to help the individual to search his own well-being. We also postulate that this commonality is not shared by other psychological models, although they have a comparable interventional and practical vein, such as cognitive-behavioral psychotherapy, which we also analyze in this paper. The results obtained are congruent with the set of hypothesis here suggested.